Strategi Pemasaran Jasa Pendidikan dalam Menarik Minat Peserta Didik Baru di SMK Dharma Agung - Riksa Iqomah; Devi Silvia Dewi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This study aims to review and describe data on the marketing mix strategy carried out by SMK Dharma Agung in increasing the interest of new students. The method used in this study is a qualitative method. The data collection in this study is interviews, observations and document studies. The data analysis techniques used are by reducing data, presenting data and drawing conclusions. The results of the study show that SMK Dharma Agung has implemented a fairly good educational marketing strategy, several programs and services offered can attract people's tastes and interests, promotional activities carried out by the school are running quite well and are managed centrally by the foundation and assisted by the principal. There are two types of promotional activities carried out, namely during PPDB and when outside PPDB. The promotion carried out during PPDB was by installing banners, pamphlets, and distributing brochures. In addition, SMK Dharma Agung also carried out promotions by visiting SMP/MTS and the community. Then for promotions that are carried out outside PPDB, namely by carrying out activities such as participating in competitions, parades when welcoming Islamic holidays by providing information about school activities and strengthening relationships with the community.